Impact of Pulsatility and Flow Rates on Hemodynamic Energy Transmission in an Adult Extracorporeal Life Support System. Issue 7 (20th April 2015) - Wolfe, Rachel; Strother, Ashton; Wang, Shigang; Kunselman, Allen R.; Ündar, Akif
Abstract This study investigated the total hemodynamic energy (THE) and surplus hemodynamic energy transmission (SHE) of a novel adult extracorporeal life support (ECLS) system with nonpulsatile and pulsatile settings and varying pulsatility to define the most effective setting for this circuit. The circuit consisted of an i‐cor diagonal pump (Xenios AG, Heilbronn, Germany), an XLung membrane oxygenator (Xenios AG), an 18 Fr Medos femoral arterial cannula (Xenios AG), a 23/25 Fr Estech RAP femoral venous cannula (San Ramon, CA, USA), 3/8 in ID × 140 cm arterial tubing, and 3/8 in ID × 160 cm venous tubing. Priming was done with lactated Ringer's solution and packed red blood cells (HCT 36%). The trials were conducted at flow rates 1–4 L/min (1 L/min increments) under nonpulsatile and pulsatile mode, with differential speed values 1000–4000 rpm (1000 rpm increments) at 36°. The pseudo patient's mean arterial pressure was kept at 100 mm Hg using a Hoffman clamp during all trials. Real‐time flow and pressure data were collected using a custom‐based data acquisition system. Mean pressures across the circuit increased with increasing flow rates, but increased insignificantly with increasing differential speed values. Mean pressure did not change significantly between pulsatile and nonpulsatile modes. Pulsatile flow created more THE than nonpulsatile flow at the preoxygenator site (P < 0.01). Of the different components of the circuit, the arterial cannula created the greatest THE loss. THE loss across the circuit ranged from 24.8 to 71.3%. Still, under pulsatile mode, more THE was delivered to the pseudo patient at low flow rates. No SHE was created with nonpulsatile flow, but SHE was created with pulsatile flow, and increased with increasing differential speed values. At lower flow rates (1–2 L/min), the arterial cannula contributed the most to SHE loss, but at higher flow rates the arterial tubing created the most SHE loss. The circuit pressure drop values across all flow rates were 33.1–246.5 mm Hg, and were slightly higher under pulsatile mode than nonpulsatile mode. The i‐cor diagonal pump creates satisfactory pulsatile and nonpulsatile flows, and can easily change the pulsatile amplitude and energy transmission. The attributes of the XLung membrane oxygenator include low resistance, low energy loss, and low pressure drops at all flow rates and differential speed values. The arterial cannula created the highest pressure drop of all components of the circuit. Pulsatile flow improved the transmission of hemodynamic energy to the pseudo patient without significantly affecting the pressure drops across the circuit.